Assessing the impact of COVID-19 on the physical activity of 10-11-year-old children and their parents: Active-6 a mixed-methods study - Russell Jago; Danielle House; Ruth Salway; Robert Walker; Lydia Emm-Collison; Kate Sansum; Katie Breheny; Sarah Churchward; Joanna G Williams; William Hollingworth; Frank de Vocht (NIHR Journals Library, 2024)
Background Physical activity is essential for long-term health, yet data from before the COVID-19 pandemic showed only 41% of 10- to 11-year-olds met the UK government's physical activity recommendations. Children's physical activity was limited during the national COVID-19 lockdowns. It is important to measure children's physical activity in the recovery period to assess the short- and medium-term impact of the lockdowns. Objectives To use mixed-methods to assess the impact of the COVID-19 pandemic on moderate-to-vigorous physical activity of year 6 children in the short-term (2021) and medium-term (2022) recovery periods by comparing these with data sampled from the same schools in 2017/18. Methods Quantitative and qualitative data were collected in two waves: wave 1 (May-December 2021), when lockdowns had finished but some COVID-19 mitigation policies were still in place, and wave 2 (January-July 2022), when most restrictions had been removed. These were compared with baseline data from similar year 6 children and parents/carers in the same schools collected between March 2017 and June 2018 (wave 0). Results In wave 1, average child accelerometer-measured weekday moderate-to-vigorous physical activity was 7-8 minutes lower than pre-pandemic while sedentary time was higher by almost 30 minutes. Child moderate-to-vigorous physical activity had recovered to pre-pandemic levels in wave 2, although sedentary time remained elevated. Across our studies, we found a new normal for child physical activity, characterised as more dependent on structured activities such as active clubs. Physical activity inequalities appear to be widening among girls and low socioeconomic position families, as they face unique barriers to participating in the new normal. Limitations Our sample includes more households with higher educational qualifications and predominantly female parents. Undertaking this research in schools while COVID-19 disruptions were ongoing created challenges to data collection which may have limited schools' and families' participation. Conclusions COVID-19 lockdowns negatively impacted child physical activity. It took almost a year of no restrictions for this to recover, and sedentary time remains high. Despite this recovery, 59% of children do not meet activity guidelines. There is a new normal to child physical activity that relies on structured activities, and some children and families may face challenges to taking part in the new normal. Strategies are needed to increase child physical activity for all. Future work Develop new ways to work in partnership with schools to design bespoke physical activity programmes that can be delivered at the school site. Develop new ways to help girls and children from lower-income households to be physically active. Find the most effective means of maximising existing school resources such as extended school provision (after-school clubs) and physical resources (equipment) to promote physical activity outside of curriculum time. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Public Health Research as award number NIHR131847. Plain language summary Why did we do this study? Physical activity can improve children's health, learning and quality of life, yet only 41% of year 6 children (aged 10-11 years) in the UK were meeting physical activity guidelines before the pandemic. COVID-19 lockdowns and restrictions meant children were unable to be active in their normal ways. We expected these restrictions to reduce children's activity while they were in place. The Active-6 project wanted to know whether any changes to children's activity lasted after the restrictions had gone. What did we do? We used devices called accelerometers to measure Year 6 children's activity in 2021 and 2022. We compared this information with data collected in 2017/18 from year 6 children from the same schools. We also interviewed parents, children and school staff to find out about their experiences and why they felt any changes had happened. What did we find? In 2021, children's activity was significantly lower than before the pandemic. The time children spent sedentary, not moving at all, was higher. By 2022, child activity returned to pre-COVID levels but their sedentary time remained high. We found that the ways in which children are active have changed since the COVID-19 lockdowns. Children spend less time doing active play and now rely more on structured activities like sports clubs. The gap in how active children are seems to be widening, with girls and low-income families being less active. What does this mean for child physical activity? It took almost a year with no restrictions for children's physical activity to recover, and sedentary time remains high. Despite this recovery, 59% of children do not meet activity guidelines. Children now rely more on clubs for their activity, and it is hard for some children and families to take part in these. Strategies are needed to increase child physical activity for all.